Actual memory as a mediator of the amyloid‐subjective cognitive decline relationship. Issue 1 (14th February 2019) - Chen, Xi; Farrell, Michelle E.; Moore, William; Park, Denise C.
ABSTRACT: Introduction: Amyloid pathology in cognitively normal adults is associated with subjective cognitive decline, potentially reflecting awareness of Alzheimer's‐related memory deficits. To clarify the mechanism underlying this relationship, we used mediational analyses to determine the role of depression, anxiety, and actual memory performance. Methods: To assess amyloid deposition, we imaged 85 cognitively normal adults with florbetapir positron emission tomography imaging. Subjective cognitive decline was measured using a multidimensional instrument that assessed seven subjective memory domains. Mediational measures included assessments of actual memory performance (current and retrospective longitudinal change), depression, and anxiety. Results: The relationship between amyloid and subjective cognitive decline was mediated by poorer memory performance and greater retrospective memory decline, not depression or anxiety. The mediational roles were significant for domains associated with memory function and memory‐related anxiety. Discussion: In individuals harboring amyloid, self‐reported beliefs of declining memory likely indicate early self‐awareness of actual worsening function rather than depression or anxiety.